Wybrane predykatory przedsiębiorczości handlowców - Cębrzyńska, Joanna; Dudek, Bohdan (Acta Universitatis Lodziensis. Folia Psychologica, 2008)
The aim of this research was to gain better understanding of the characteristics of individuals inclining towards setting up their own business. Because of a nature of this paper we restrict ourselves to analyzing the career anchors and locus of control. We claim that those variables affect one’s motivation and so determine individual behaviour (entrepreneurial behaviour as well). Also demographic factors such as: age, sex and education were included to the model to control their influence on a dependent variable. The study was conducted in commercial centre, both on business owners and workers employed. The aim of the research was to specify which of the considered variables allow us to predict a probability of being an entrepreneur – what are the typical traits of a person who starts a new venture. Obtained results show that the probability of being an entrepreneur is related to internal locus of control and one of the career anchor – creativity.